Т. М. Tyshchenko: ANALYTICAL NOMINATIONS IN EASTERN PODILLYA DIALECTS - TYSHCHENKO. , T. M. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Introduction. The study of nomination processes in dialects is one of the important problems of modern dialectology. The analysis of scientific works on nomination processes in the dialects of the Ukrainian language made it possible to identify general approaches to the interpretation of their course and results. Purpose. The purpose of the research is to identify the composite nominations recorded in the dictionaries of the dialects of the Eastern Podillya area, to determine their motivational models and connections with one-word nouns. Methods. The use of comparative and descriptive methods makes it possible to trace the contents of different thematic groups of vocabulary with a composite nomination, to determine the structural and semantic models characteristic of each of the analyzed groups. Results. The article analyzes the author’s printed «Vocabulary of beekeeping dialects of Eastern Podillya», «Eastern Podillya maternity rite: lexicographic and textual descriptions» and manuscript dictionaries «Vocabulary of fishing in the dialects of Eastern Podillya», «Vocabulary of animal husbandry in the dialects of Eastern Podillya». It has been noted that in the thematic groups of vocabulary with a specific meaning there are more compound nouns than in the thematic group of ritual vocabulary, due to extralingual reality, questionnaires and methods by which dialect material was collected. It has been determined that in all the studied groups mostly the analytical nouns have been fixed that were formed according to the model «noun + adjective», in particular, to denote the archetypes fish, animal, bee, child, woman. Originality. The compound nouns of thematic groups of the vocabulary of beekeeping, fishing, animal husbandry and maternity rites in the Eastern Podillya dialects, which have not been described yet, are analyzed. It has been found out that analytical nominations are a creative basis for complex names and monolexems. Conclusion. It has been determined that the groups of this vocabulary are equally filled with compound nominations of different constructions. Their functioning in the dialects is due to a set of differential features. We see the prospect of the investigation in the study of the mechanisms of formation of the composite nomination in other thematic groups of the vocabulary of Eastern Podillya dialects.